Excess mortality related to circulatory system diseases and diabetes mellitus among Italian AIDS patients vs. non-AIDS population: a population-based cohort study using the multiple causes-of-death approach - Barbara Suligoi; Saverio Virdone; Martina Taborelli; Luisa Frova; Enrico Grande; Francesco Grippo; Marilena Pappagallo; Vincenza Regine; Lucia Pugliese; Diego Serraino; Antonella Zucchetto (BMC Infectious Diseases, 2018)
Abstract Background Chronic diseases, chiefly cancers and circulatory system diseases (CSDs), have become the leading non-AIDS-related causes of death among HIV-infected people, as in the general population. After our previous report of an excess mortality for several non-AIDS-defining cancers, we now aim to assess whether people with AIDS (PWA) experience also an increased mortality for CSDs and diabetes mellitus (DM), as compared to the non-AIDS general population (non-PWA). Methods A nationwide, population-based, retrospective cohort study was conducted including 5285 Italians, aged 15−74 years, who were diagnosed with AIDS between 2006 and 2011. Multiple cause-of-death (MCoD) data, i.e. all conditions reported in death certificates, were retrieved through record-linkage with the National Register of Causes of Death up to 2011. Using MCoD data, sex- and age-standardized mortality ratios (SMRs) with 95% confidence intervals (CIs) were calculated by dividing the observed number of PWA reporting a specific disease among MCoD to the expected number, estimated on the basis of mortality rates (based on MCoD) of non-PWA. Results Among 1229 deceased PWA, CSDs were mentioned in 201 (16.4%) certificates and DM in 46 (3.7%) certificates among the various causes of death. These values corresponded to a 13-fold higher mortality related to CSDs (95% CI 10.8–14.4) and DM (95% CI: 9.5–17.4) as compared to 952,019 deceased non-PWA. Among CSDs, statistically significant excess mortality emerged for hypertension (23 deaths, SMR = 6.3, 95% CI: 4.0–9.4), ischemic heart diseases (39 deaths, SMR = 6.1, 95% CI: 4.4–8.4), other forms of heart diseases (88 deaths, SMR = 13.4, 95% CI: 10.8–16.5), and cerebrovascular diseases (42 deaths, SMR = 13.4, 95% CI: 9.7–18.2). The SMRs were particularly elevated among PWA aged < 50 years and those infected through drug injection. Conclusions The use of MCoD data disclosed the fairly high mortality excess related to several CSDs and DM among Italian PWA as compared to non-PWA. Study findings also indicate to start preventive strategies for such diseases at a younger age among AIDS patients than in the general population and with focus on drug users.